2016
DOI: 10.5539/ijbm.v11n12p230
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Relationship Continuity: A Mediational Study of Relationship Quality and Word of Mouth

Abstract: Employees are claimed to be one the important strategic key asset of organization. In today's competitive world, departing of the skilled employees is immense dilemma for organizations especially at managerial level.Organizations not have only bear the cost of hiring and training of these mangers but also these managers act as intellectual capital as they possess knowledge and information of the key strategic areas. This study attempts to study the factors such as self-efficacy, work environment and workplace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
2
3
0
2
Order By: Relevance
“…Thus, H3, stating that perceived security affects e-service quality, and H4, stating that perceived security affects citizen satisfaction, are accepted. The results of this study are supported by empirical evidence from the research of Jin and Park (2006) and Chung and Shin (2009), who found a positive effect of security on online citizen satisfaction.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Thus, H3, stating that perceived security affects e-service quality, and H4, stating that perceived security affects citizen satisfaction, are accepted. The results of this study are supported by empirical evidence from the research of Jin and Park (2006) and Chung and Shin (2009), who found a positive effect of security on online citizen satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, Jin and Park (2006) revealed a positive effect of security on online citizen satisfaction. The results of this study are supported by empirical evidence from the studies of Chung and Shin (2009); Chung and Shin (2010).…”
Section: Perceived Security E-service Quality and Satisfactionsupporting
confidence: 79%
See 3 more Smart Citations